THE PROCESS OF THE PARADOXICAL DISSONANCE AND DESIGN IN THE ENTREPRENEURSHIP ACTION: A CONTRIBUTION TO THE STUDIES OF THE PARADIGM OF COMPLEXITY (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
In this work, the objective is to shed light on little-studied concepts in the research of entrepreneurship: the concepts of design and paradoxical dissonance. Therefore, we propose to the scientific community of entrepreneurship the paradigm of paradoxical dissonance in the thought processes of the entrepreneur, where to resolve intra-psychic conflict we use what we call the design process. Therefore, in the design process, the entrepreneur participates in the work of mental representations, adding to the projective thought and definition of the business project. The present document deals with, through the mental process of design, a reaffirmation of the entrepreneur and giving importance to the entrepreneur as a cognitive and social individual who operates in complexity. We approach complexity and entrepreneurial thought based on the perspective of Edgar Morín (1988). We reflect on the social and mental construction of the entrepreneur, and what makes the existence of paradoxical dissonance possible. We analyze processes of design in the entrepreneur as a useful element to direct the thought of the entrepreneur and help him to represent, define, and problematize his or her entrepreneurial project. Therefore, the article achieves the integration of the two cognitive mechanisms of the entrepreneur, paradoxical dissonance and design, and we propose a model of the two cognitive mechanisms at play.